Primary lymphedema of the left lower limb in a new-born boy: a case report - Sharath, A. P.; Ghritlaharey, Rajendra K. (International Surgery Journal, 2022)
A 7-day-old boy was admitted with a history of swelling involving his left lower limb since birth. He was born normally to a Gravida 1, Para-0, to a 22-years-old mother. Antenatal history was nothing significant. His clinical examination revealed left lower limb swelling and was suggestive of primary lymphedema. It involved from the ankle area up to the groin of the left side of the limb. His right lower limb and both upper limbs were normal. His other systemic examination was also normal. He was treated with aseptic needle aspiration of the lymphatic fluid, and a compression dressing was applied. He suddenly died of an unknown reason while sleeping at around 4.00 AM on the third post aspiration day.